Primary exploration of host–microorganism interaction and enteritis treatment with an embedded membrane microfluidic chip of the human intestinal–vascular microsystem - Zhao, Wei; Yao, Yuhan; Zhang, Tong; Lu, Huijun; Zhang, Xinlian; Zhao, Linlin; Chen, Xi; Zhu, Jinhui; Sui, Guodong; Zhao, Wang (Frontiers in Bioengineering and Biotechnology, 2022)
Intestinal flora plays a crucial role in the host’s intestinal health. Imbalances in the intestinal flora, when accompanied by inflammation, affect the host’s intestinal barrier function. Understanding it requires studying how living cells and tissues work in the context of living organs, but it is difficult to form the three-dimensional microstructure intestinal–vascular system by monolayer cell or co-culture cell models, and animal models are costly and slow. The use of microfluidic-based organ chips is a fast, simple, and high-throughput method that not only solves the affinity problem of animal models but the lack of microstructure problem of monolayer cells. In this study, we designed an embedded membrane chip to generate an in vitro gut-on-a-chip model. Human umbilical vein endothelial cells and Caco-2 were cultured in the upper and lower layers of the culture chambers in the microfluidic chip, respectively. The human peripheral blood mononuclear cells were infused into the capillary side at a constant rate using an external pump to simulate the in vitro immune system and the shear stress of blood in vivo. The model exhibited intestine morphology and function after only 5 days of culture, which is significantly less than the 21 days required for static culture in the Transwell® chamber. Furthermore, it was observed that drug-resistant bacteria triggered barrier function impairment and inflammation, resulting in enteritis, whereas probiotics (Lactobacillus rhamnosus GG) improved only partially. The use of Amikacin for enteritis is effective, whereas other antibiotic therapies do not work, which are consistent with clinical test results. This model may be used to explore intestinal ecology, host and intestinal flora interactions, and medication assessment.